2008
DOI: 10.1177/0731684408090378
|View full text |Cite
|
Sign up to set email alerts
|

Tensile Creep and Deformation Modeling of Vinyl Ester Polymer and Its Nanocomposite

Abstract: This article discusses tensile creep behavior of vinyl ester polymer and its nanocomposite with 0.5 wt% functionalized carbon nanofibers. It is shown that for a constant temperature the creep resistance decreases with increasing stress. At lower temperature, higher creep compliance was observed for vinyl ester as compared to nanocomposite, while at temperatures close to T g of vinyl ester creep compliance in nanocomposite was higher than that for vinyl ester. An analytical power-law relationship was used to pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 57 publications
(37 citation statements)
references
References 6 publications
1
35
1
Order By: Relevance
“…Some of these models were reviewed in Refs. [27] and [28]. The power law models have evolved over the years in order to be applicable to a wider range of temperatures, stress levels, and polymeric materials [29e31].…”
Section: Creep Strain-time Behavior and Predictionsmentioning
confidence: 99%
“…Some of these models were reviewed in Refs. [27] and [28]. The power law models have evolved over the years in order to be applicable to a wider range of temperatures, stress levels, and polymeric materials [29e31].…”
Section: Creep Strain-time Behavior and Predictionsmentioning
confidence: 99%
“…It was observed that incorporation of the reinforcement in the polypropylene matrix reduced both the amount and the rate of creep strain. Plaseied and Fatemi used Findley's power law to represent short‐terms (up to 100 h) tensile creep behaviour of vinyl ester polymer and its nanocomposites with 0.5% functionalized carbon nanofibres at different temperatures and stress levels. The constants m and n were represented by: normallog0.12em()m0.5emitalicor0.5emn=a+bT+cσ+dσT where a , b , c and d are material constants.…”
Section: Creep Behaviourmentioning
confidence: 99%
“…Applicability of these models is limited to the small range of composites and only for short term linear creep. Experimental observations for different polymers and their composites were the key factor in these studies [3,[9][10][11][12]. Some investigations focused on nonlinear viscoelastic behavior of polymers and their composites while single layer has been analyzed [13,14].…”
Section: Introductionmentioning
confidence: 99%